Aflatoxin contamination of human breast milk and complementary foods in southern Ethiopia - Eshete, Mesfin (Matern Child Nutr, 2020)
Exposure to unsafe level of aflatoxin in early life may lead to growth faltering. However, the extent of contamination of breast milk and complementary foods is poorly examined. We determined aflatoxin M(1) (AFM(1)) and B(1) (AFB(1)) contamination of human breast milk and cereal‐based cooked complementary foods, respectively, among households having children 6–23 months of age in Sidama zone, southern Ethiopia. Data were collected through two cross‐sectional surveys implemented in the wet (n = 180) and dry (n = 180) seasons. Eligible households (n = 360) were recruited from three agroecological zones (lowland, midland and highland, each with sample size of 120) using a multistage sampling technique. AFB(1) and AFM(1) levels were determined using enzyme‐linked immunosorbent assay. Mann–Whitney U and Kruskal–Wallis tests were performed to compare aflatoxin levels between seasons and across the agroecological zones. Among 360 breast milk samples tested, 64.4% had detectable AFM(1) and 5.3% exceeded the 0.025 parts per billion (ppb) limit set by the European Union for infant milk. The median AFM(1) in the lowlands was significantly higher than in the other agroecological settings (P < 0.001). By season, AFM(1) was higher in breast milk samples collected in the dry season (P = 0.041). AFB(1) was detected in 96.4% of the food samples tested, and 95.0% had concentration exceeding the permissible European Union limit of 0.1 ppb. The median AFB(1) was significantly higher in the lowland (P = 0.002), but there was no difference between the seasons (P = 0.386). The study indicated that, in southern Ethiopia, foods intended for infants are heavily contaminated with AFB(1). Contamination of breast milk is also a significant health concern.